Portrait of the All-American Girl in Time: The Contradictions Between 1950s Gender Ideology and Style in Serenteen Magazine - Lewandowski, Tadeusz (Stylistyka, 2021)
“Portrait of the All-American Girl in Time: The Contradictions Between 1950s Gender Ideology and Style in Seventeen Magazine, by Tadeusz Lewandowski, examines the ideał of adolescent femininity constructed by Seventeen magazine in the decade of the 1950s. Seventeen, First published in 1944, was the first periodical directed at teenage girls during the postwar era, and has until today remained the most popular. From its immediate in- ception during World War II it promoted a vision of the American girl as independent, and spoke out against gender inequality, much in keeping with the war emergency govem- ment propaganda of the time. However, by the 1950s Seventeen had been transformed from an organ that endorsed the emancipation of women from traditional gender roles to one that fully promoted the role of housewife as the single legitimate goal for young women. This was in accordance with the prevailing theories that emerged after the war as to women’s natural inclination to domesticity and motherhood, and the feminine ideał that appeared with it. To this, Seventeen added a consciously constructed ideał of adolescent femininity that its readers were expected to conform to, existing within the confines of a larger gender ideology that placed boys in a dominant position and encouraged physical beautification and allure. This paper explores Seventeen ’s adolescent feminine ideał and its roots, and also examines the contradictions between its emphasis on chastity and inno- cence, and the sexually charged clothing and make up styles that young women were urged to adopt within Seventeen ’s pages.